Sistem Ekonomi (Islam) dan Pelarangan Riba dalam Perspektif Historis - Risanda Alirastra Budiantoro; Riesanda Najmi Sasmita; Tika Widiastuti (Jurnal Ilmiah Ekonomi Islam, 2018)
Allah has given the guidance in the form of Islam for Muslim to take and lead all the aspects of life including the economic activity. The Islamic economic system is believed to be the answer of the economic problems that exist at this time. The goal is to achieve falah in kaffah by not doing some economic activities that are in violation as prescribed by Islam. For example is riba. Discourse on riba can be said "classical" both in the development of Islamic thought and in Islamic civilization because riba often occurs in all aspects of public life, especially economic transactions (in Islam called muamalah). Riba is an additional retrieval, either in a sale and purchase transaction or lending in a false or contrary to the principle of muamalah in Islam. Prohibition of riba is obtained from various sources by the Qur'an and Hadith Rasulullah SAW, so the scholars firmly and clearly defined the prohibition of riba because there are exploitative elements that can harm the others. So, this study is aimed to identif yIslamic economic system and the prohibition of riba in historical perspective. From the results of this study is expected to be a good reference for the reader to understand the Islamic economic system and riba in the future.Saran sitasi: Budiantoro, R., Sasmita, R., & Widiastuti, T. (2018). Sistem Ekonomi (Islam) dan Pelarangan Riba dalam Perspektif Historis. Jurnal Ilmiah Ekonomi Islam, 4(01), 1-13. doi: http://dx.doi.org/10.29040/jiei.v4i1.138